Análisis del control interno en cuentas por cobrar de la empresa Travel Industry Advisor S.A. Traninad - Estrella Cevallos, Ezequiel David (2021)
The internal control within an organization is the key piece of the perfect functioning and economic well-being of the same since it allows to buy and analyze each department of the company thus avoiding the existence of fraud, waste of funds or loss of its assets as well as it also makes it possible to efficiently detect any deviations that are present. The evaluation of the internal control within the company, allows to carry out tests of effectiveness and efficiency of its systems, be these accounting, administrative or financial. Within the commercial sector, organizations that achieve higher margins of income tend to have more financial profitability, since they maximize their income and minimize costs, thus obtaining a high economic profitability. To carry out the present analysis, the importance of carrying out a financial study through the horizontal exploration of its main accounts was taken into account, in addition to using financial ratios that are of enormous help to achieve more efficient knowledge of the shortcomings in an entity, without However, the inquiry procedure that was used has been the inductive one, which focuses first on the observation of facts, then on the study of them and finally the conclusion of the results, fundamentally this is the procedure that allowed to conclude in a concrete way the present inquiry.